Desmethyl bosentan displays a similar in vitro interaction profile as bosentan - Weiß, Johanna; Baumann, Sybille; Theile, Dirk; Haefeli, Walter E. (Pulmonary pharmacology and therapeutics, 2015)
The endothelin-1 receptor antagonists bosentan and ambrisentan used for the treatment of pulmonary arterial hypertension remarkably differ in their potential to act as perpetrators in pharmacokinetic drug-drug interactions. So far, it is not clear whether the metabolites of bosentan and ambrisentan contribute to the extent of drug interactions. We therefore investigated the effects of 4-hydroxymethyl ambrisentan, hydroxy bosentan, desmethyl bosentan, and hydroxy desmethyl bosentan on targets which are inhibited or induced by the parent compounds. The hydroxylated metabolites of ambrisentan and bosentan neither induced any of the genes investigated at the mRNA level, nor inhibited P-glycoprotein (P-gp) measured by calcein assay in L-MDR1 cells, and only weakly inhibited organic anion transporting polypeptide (OATP) 1B1 and OATP1B3 measured by 8-fluorescein-cAMP uptake in HEK-OATP1B1 and HEK-OATP1B3 cells. In contrast, desmethyl bosentan induced mRNA expression of cytochrome P450 3A4 (CYP3A4, about 6-fold at 50 μM), ABCB1 (P-gp, about 4.5-fold at 50 μM), and ABCG2 (breast cancer resistance protein, about 2-fold at 50 μM), whereas CYP2C19, ABCB11, and ABCC2 (multidrug resistance-associated protein 2) were not induced in LS180 cells. In a reporter gene assay, desmethyl bosentan activated pregnane X receptor with the highest potency of all metabolites tested. Whereas desmethyl bosentan did not inhibit P-gp, it inhibited OATP1B1 with an IC50 of 3.8 μM (1.9-7.6) (geometric mean, 95% CI) and OATP1B3 with an IC50 of 7.4 μM (2.6-21.52). In conclusion, our data demonstrate that desmethyl bosentan exhibits a similar pharmacokinetic interaction profile as bosentan and might contribute to the inducing effects of the parent compound.
Available online 19 December 2014
Gesehen am 30.06.2020